Associations between psychosocial factors and incidence of sexually transmitted disease among South African adolescents - O’Leary, Ann (Sex Transm Dis, 2015)
BACKGROUND: Adolescents living in South Africa are at high risk for HIV and other sexually transmitted disease (STD). The present study sought to identify correlates of curable STD incidence among a cohort of adolescents in Eastern Cape Province, South Africa. METHODS: Data were collected in conjunction with an HIV/STD prevention intervention randomized controlled trial(1). At 54 months post-intervention, curable STD incidence (gonorrhea, chlamydial infection and trichomoniasis) was assayed and self-report measures of potential correlates of STD incidence were collected. RESULTS: Participants were adolescents reporting at least one sexual partner in the past 3 months (N = 659). As expected, univariate analyses revealed that girls were more likely than boys to have an STD. In addition, intimate partner violence, unprotected sex, and having older partners were associated with incident STD. In Poisson multiple regression analyses, gender (risk ratio [RR] = 4.00, 95% confidence interval [CI]: 2.51–6.39), intimate partner violence (RR = 1.23, 95% CI: 1.12–1.35), unprotected sex (RR = 1.42, 95% CI: 1.09–2.01), and multiple partners (RR = 1.70, 95% CI: 1.11–2.61), but not partner’s age (RR = 1.00, 95% CI: 0.94–1.07) were associated with incident STD, adjusting for 42-month STD prevalence. Binge drinking, forced sex, and age were unrelated to STD incidence in both analyses. Interactions between gender and the hypothesized correlates were non-significant, suggesting that gender did not modify these relationships. CONCLUSIONS: Interventions to reduce HIV/STD incidence among adolescents in South Africa should address the risk associated with gender, unprotected sex, intimate partner violence, and multiple partnerships.